Balance rehabilitation with a virtual reality protocol for patients with hereditary spastic paraplegia: Protocol for a clinical trial. - Bianca Simone Zeigelboim; Maria Renata José; Geslaine Janaina Bueno Dos Santos; Maria Izabel Rodrigues Severiano; Hélio Afonso Ghizoni Teive; José Stechman-Neto; Rosane Sampaio Santos; Cristiano Miranda de Araújo; Bianca Lopes Cavalcante-Leão (PLoS ONE)
Background Neurodegenerative diseases are sporadic hereditary conditions characterized by progressive dysfunction of the nervous system. Among the symptoms, vestibulopathy is one of the causes of discomfort and a decrease in quality of life. Hereditary spastic paraplegia is a heterogeneous group of hereditary degenerative diseases involving the disorder of a single gene and is characterized by the progressive retrograde degeneration of fibers in the spinal cord. Objective To determine the benefits of vestibular rehabilitation involving virtual reality by comparing pre intervention and post intervention assessments in individuals with hereditary spastic paraplegia. Methods In this randomized controlled clinical trial from the Rebec platform RBR-3jmx67 in which allocation concealment was performed and the evaluators be blinded will be included. The participants will include 40 patients diagnosed with hereditary spastic paraplegia. The interventions will include vestibular rehabilitation with virtual reality using the Wii® console, Wii-Remote and Wii Balance Board (Nintendo), and the studies will include pre- and post intervention assessments. Group I will include twenty volunteers who performed balance games. Group II will include twenty volunteers who performed balance games and muscle strength games. The games lasted from 30 minutes to an hour, and the sessions were performed twice a week for 10 weeks (total: 20 sessions). Results This study provides a definitive assessment of the effectiveness of a virtual reality vestibular rehabilitation program in halting the progression of hereditary spastic paraplegia, and this treatment can be personalized and affordable. Conclusion The study will determine whether a vestibular rehabilitation program with the Nintendo Wii® involving virtual reality can reduce the progressive effect of hereditary spastic paraplegia and serve as an alternative treatment option that is accessible and inexpensive. Rebec platform trial: RBR-3JMX67.